Women's experiences of being invited to participate in a case-control study of stillbirth - findings from the Midlands and North of England Stillbirth Study - Jayne Budd; Tomasina Stacey; Bill Martin; Devender Roberts; Alexander E. P. Heazell (BMC, 2018)
Abstract Background The Midlands and North of England Stillbirth Study (MiNESS) was a case-control study of women who had a stillbirth or who had an ongoing pregnancy. During the set up phase questions were raised about whether interviewing women within six weeks of a stillbirth and recruiting women who were still pregnant into a "stillbirth" study was acceptable. This led to the research questions "whether it is appropriate to ask women who have recently experienced a stillbirth to participate in research?" and "whether it is appropriate to ask pregnant women to participate in a research project looking at factors associated with stillbirth." This nested study aimed to describe the opinions of women approached to participate in MiNESS to explore their views and experiences of a research project focussed on stillbirth. Methods Semi- structured interviews were conducted at a single study site involved in MiNESS. Purposive sampling was used to obtain a sample of women who were approached following a stillbirth (case n = 6) and those who were approached during pregnancy who gave birth to a live born baby (control n = 6). These two groups of women were divided equally according to whether they participated in the main MiNESS questionnaire study and those who declined to do so (n = 3 in each group). Interview data were transcribed and analysed using thematic analysis to identify the most important factors in determining whether women participated in MiNESS. Results The following themes emerged from the analysis: participants' understanding of research; approach by researcher; wanting to help; stillbirth taboo. These themes are explored individually in the manuscript. Participants reported positive views about research and previous participation in research studies. Respondents valued an initial approach from a member of staff already known to them. The taboo around stillbirth was a barrier to participation for some women with ongoing pregnancies. Conclusions Experiences and views regarding research differed between participants and non-participants in the MiNESS study. Participants reported a greater understanding of the importance and implications of clinical research. When designing future studies, the timing of approach, clarity of information and the person approaching potential participants should be considered to optimise recruitment. Trial registration NCT02025530 date registered: 01/01/2014.